Does immigration affect wages? A look at occupation-level evidence - Pia M. Orrenius; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2003)
Previous research has reached mixed conclusions about whether higher levels of immigration reduce the wages of natives. This paper reexamines this question using data from the Current Population Survey and the Immigration and Naturalization Service and focuses on differential effects by skill level. Using occupation as a proxy for skill, the authors find that an increase in the fraction of workers in an occupation group who are foreign born tends to lower the wages of low-skilled natives-particularly after controlling for endogeneity-but does not have a negative effect among skilled natives.
Keywords: 330; Immigrants; Wages; Employment (Economic theory)